Builders of modern India: Gandhi his life and thought - Kripalani, J. B.; Publication Division; Edited by Chatterjee, Roma (New Delhi Publications Division, Ministry of Information and Broadcasting, GOI, 2019)
There are books that transform themselves from ordinary to an icon. This is one such title. Gandhi- His Life and Thought does not only outline and piece together the outlines of the Mahatma's life but explains in some detail the Gandhian philosophy. Gandhi's views on Satyagraha, Khadi, and Charkha, to name the prominent ones, have been discussed at length in the second part of the book. The author, J. B. Kripalani or Jivatram Bhagwandas Kripalani (1888-1982) popularly called Acharya Kripalani was a close associate of Gandhi but an objective Gandhian. A teacher at the core, he was a lecturer in various colleges and BHU before becoming the Principal of Gujarat Vidyapeeth after which he came to be called Acharya. He was the Congress party President during the transfer of power during 1946-47 yet became the worst critic of the Central Governments after 1950. Acharya Kripalani is the front ranker in the generations of dissenters from the Non-Cooperation Movement during the freedom movement to the successive governments.
Keywords: Mahatma Gandhi; Nation Maker